The Alteration of T-Cell Heterogeneity and PD-L1 Colocalization During dMMR Colorectal Cancer Progression Defined by Multiplex Immunohistochemistry - Yan, Hongkai; Li, Yaqi; Wang, Xiaoyu; Qian, Juanjuan; Xu, Midie; Peng, Junjie; Huang, Dan (Frontiers in Oncology, 2022)
Background Immune checkpoint inhibitors (ICIs) are quickly becoming key instruments in the treatment of mismatch repair-deficient (dMMR) colorectal cancers (CRCs). Despite their clinical value, ICIs have several limitations associated with their use. Only approximately 15% of all CRCs have a dMMR status, and the overall response rate of ICIs is approximately 40%. The mechanism of ICI resistance is not clear, and its study is limited by the lack of information available on the characterization of the immune microenvironment during the progression from early- to advanced-stage dMMR CRC. Methods We used multiplex immunohistochemistry (mIHC) with two panels, each containing five markers, to simultaneously analyze the proportions of immune microenvironment constituents in 59 patients with advanced-stage dMMR CRC and 24 patients with early-stage dMMR CRC. We detected immune cell–associated signatures in the epithelial and stromal regions and evaluated the predictive value of these immune molecules. Student’s t-tests, Mann–Whitney U tests, Cox proportional hazards regression modeling, univariate Cox modeling, and Kaplan–Meier estimation were used to analyze immune cell proportions and survival data. Results We observed significantly higher proportions of CD8+ cytotoxic T cells (CD8+) (p = 0.001), CD8+ memory T cells (CD8+CD45RO+) (p = 0.032), and CD4+ regulatory T cells (CD4+FOXP3+) (p = 0.011) in the advanced-stage dMMR CRCs than in the early-stage dMMR CRCs. Furthermore, CD3+ T cells with PD-L1 colocalization (CD3+PD-L1+) (p = 0.043) and CD8+ T cells with PD-L1 colocalization (CD8+PD-L1+) (p = 0.005) were consistently more numerous in patients in the advanced stage than those in the early stage. Our analyses revealed that a high proportion of CD3+PD-1+ T cells was an independent prognostic factor of overall survival (OS) [hazard ratios (HR) = 9.6, p < 0.001] and disease-free survival (DFS) (HR = 3.7, p = 0.010) in patients in the advanced stage. Conclusion High numbers of CD8+ cytotoxic T cells and CD8+ memory T cells, which usually represent a cytotoxic function of the adaptive immune system and possibly enhanced inhibition factors, such as CD4+ regulatory T cells and PD-L1 colocalized T cells, were associated with the transformation of the immune microenvironment from the early stage to the advanced stage in dMMR CRCs. Furthermore, CD3+PD-1+ T cells are a prognostic factor for patients with dMMR.